PURIFICAÇÃO DE NANOTUBOS DE CARBONO - Seixas, André Luís da Rosa (2010)
Carbon Nanotubes (CNT) are obtained by the folding of one or many graphene leaves, in nanometric dimensions resulting in one tube of simple walls (SWNTC) or multiple walls (MWNTC). The electric, magnetic, optic and mechanic properties make the carbon nanotubes more fascinating and attractive to many applications, mainly in the nanotechnology area. In the synthesis process, with the NTCs formed, there are catalyst residues, soot and fullerenes. Thus, this paper had as aim to evaluate the NTC purification process, using oxidation with nitric and chloride acids (concentrated and diluted) with heating by microwave. In each 100mg sample, they were added 6mL of acid, in quartz tubes. After, the samples were irradiated for 0,10,20,40 and 60 minutes, in a 1400W potency (Multiwave 3000®, Paar, Graz, Austria). In the final solutions, nickel and lanthanum were determined by the spectrometry technique of optical emission with inductively coupled plasma (ICPOES). In order to evaluate the carbonacea impurity elimination and the NTCs integrity, it was used the Raman spectroscopy technique, gravimetric thermal analysis, transmission electronic microscopy and scanning electronic microscopy. Better La and Ni extraction were obtained when it was used HNO3, concentrated with 10 minutes irradiation, eliminating the carbonacea impurities without commitment in the NTC structure.